Characteristics of Integrons and Associated Gene Cassettes in Antibiotic‐Resistant Escherichia coli Isolated from Free‐Ranging Food Animals in China. Issue 8 (23rd June 2017) - Rehman, Mujeeb Ur; Zhang, Hui; Huang, Shucheng; Iqbal, Muhammad Kashif; Mehmood, Khalid; Luo, Houqiang; Li, Jiakui
Abstract: We investigated the occurrence of integrons in antibiotic‐resistant Escherichia coli strains isolated from free‐ranging food animals, including yaks, piglets, and chickens, in China, and characterized the gene cassettes harbored within the integrons. We examined 432 E. coli strains that exhibited resistance to at least one class of antibiotics. Integrase genes and associated gene cassettes were characterized by polymerase chain reaction (PCR) analysis, restriction fragment‐length polymorphism, DNA sequencing, conjugation experiments, and plasmid analysis. Twenty‐nine (6.7%) integrons were amplified from the 432 antimicrobial‐resistant (AMR) isolates evaluated. Specifically, class 1 and 2 integrons were detected in 26 (6%) and 3 (0.7%) strains, respectively. Meanwhile, 6 different gene cassettes, dfrA1, dfr12, aadA1, aadA2, sat1, and orfF, were detected within 6 variable regions (VRs), of which the dfrA1 + aadA1 array was the most common, identified in 12 of 26 class 1 integrons (46.1%). Meanwhile, only one class 2 integron contained a cassette, and the remaining two contained undetermined VRs. Finally, a conjugation assay confirmed the transfer of 4 different types of class 1 integrons into recipient strains, with plasmid sizes ranging from 20 to 30 kb. This is the first report examining the baseline AMR characteristics of E. coli within an extensive farming system of livestock animals in China. Given that integrons were detected in >6% of resistant E. coli strains, precautionary measures are required to prevent the spread of mobile genetic resistance determinants in food animals and monitor their emergence.